In Vivo and In Vitro Impact of Carbohydrate Variation on Human Follicle-Stimulating Hormone Function - Bousfield, George R.; May, Jeffrey V.; Davis, John S.; Dias, James A.; Kumar, T. Rajendra (Frontiers in Endocrinology, 2018)
Human FSH exhibits both macro- and micro-heterogeneity in its carbohydrate moieties. Macroheterogeneity results in three physiologically relevant FSH subunit variants that possess a single N-linked glycan at either one of the two L1 loop glycosylation sites, or both glycans. Microheterogeneity is characterized by 80 to over 100 unique oligosaccharide structures attached to each of the 3 to 4 occupied N-glycosylation sites. With respect to its receptor, partially glycosylated (hypo-glycosylated) FSH variants exhibit higher association rates, greater apparent affinity, and greater occupancy than fully glycosylated FSH. Higher receptor binding activity is reflected by greater in vitro bioactivity and, in some cases, greater in vivo bioactivity. Partially glycosylated pituitary FSH shows an age-related decline in abundance that may be associated with decreased fertility. In this review, we describe an integrated approach involving genetic models, in vitro signaling studies, FSH biochemistry, relevance of physiological changes in FSH glycoform abundance, and characterize the impact of FSH macroheterogeneity on fertility and reproductive aging. We will also address the controversy with regard to claims of a direct action of FSH in mediating bone loss especially at the peri- and post-menopausal stages.